Hybrid manufacturing of stiffening grooves in additive deposited thin parts - Cristino, Valentino A. M. (2021)
This paper is focused on the hybridization of additive manufacturing with single-point incremental forming to produce stiffening grooves in thin metal parts. An analytical model built upon in-plane stretching of a membrane is provided to determine the tool force as a function of the required groove depth and to estimate the maximum allowable groove depth that can be formed without tearing. The results for additively deposited stainless-steel sheets show that the proposed analytical model can replicate incremental plastic deformation of the stiffening grooves in good agreement with experimental observations and measurements. Anisotropy and lower formability caused by the dendritic-based microstructure of the additively deposited stainless-steel sheets justifies the reason why the maximum allowable depth of the stiffening grooves is approximately 27% smaller than that obtained for the wrought commercial sheets of the same material that are used for comparison purposes.